Longitundal echo monitoring in fetus with phenotypical marfan syndrome, helpful for perinatal management - case presentation and literature review - Zych-Krekora, Katarzyna; Wójtowicz, Anna; Krekora, Michał; Słodki, Maciej; Gentillon, Hugues; Respondek-Liberska, Maria (Prenatal Cardiology, 2016)
It was the second pregnancy of an otherwise healthy married couple. The fetus (male) had detailed echocardiography monitoring in the second half of the pregnancy due to progression of cardiomegaly, and echocardiographic features of congestive heart failure. Marfan syndrome was suspected based on cardiac anomalies. For the first time, the rupture of aneurysm of aortic sinus Valsalva was documented. Despite transplacental treatment with digoxin there was fetal demise at the 34th week of gestation and postmortem newborn phenotype confirmed prenatal diagnosis. Marfan Syndrome is a rare genetic anomaly which can be diagnosed prenatally by detailed echocardiography, usually with bad prognosis (just opposite to “benign”case diagnosed later on in life span). The most common prenatal cardiac manifestations are cardiomegaly with signs of cardiac insufficiency. We present the case with new echocardiographic features.